2008
DOI: 10.1007/s00421-008-0943-z
|View full text |Cite
|
Sign up to set email alerts
|

Upper body power as a determinant of classical cross-country ski performance

Abstract: The purpose of this study was to evaluate the relationship between short (< or =60 s) and long duration (4-12 min) measures of upper body power (UBP) and mass start classical cross-country ski performance. Several experienced skiers (eight men, five women) completed three separate tests of UBP on a double poling ergometer: two tests of highest average power output for 10 s (UBP(10)) and 60 s (UBP(60)), and an incremental test to exhaustion to measure peak oxygen uptake (VO(2PEAK)) and peak power output (UBP(PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 29 publications
(59 reference statements)
3
27
1
3
Order By: Relevance
“…As both aerobic (Ingjer, 1991;Rusko, 1987) and upper body power (Alsobrook & Heil, 2009; Mahood, Kenefik, Kertzer., & Quinn, 2001; Nesser, Chen, Serfass., & Gaskill, 2004) correlate well with cross-country skiing performance, periodical assessment of these variables may indicate a skier's current performance capabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As both aerobic (Ingjer, 1991;Rusko, 1987) and upper body power (Alsobrook & Heil, 2009; Mahood, Kenefik, Kertzer., & Quinn, 2001; Nesser, Chen, Serfass., & Gaskill, 2004) correlate well with cross-country skiing performance, periodical assessment of these variables may indicate a skier's current performance capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Several upper body sprint and endurance tests using customised ski-ergometer protocols reportedly predict double poling performance on snow ( . However, these protocols often use a modified Concept II rowing ergometer to replicate the double poling technique (Holmberg & Nilsson, 2008;Alsobrook & Heil, 2009). To our knowledge, no studies to date have evaluated an incremental double poling protocol using the now commercially available Concept II upright ski-ergometer.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that elite cross-country skiers have highest values in endurance athletes [5,6]. The relevance of VO2max, time to exhaustion, lactate thresholds, upper body power output, and peak upper body oxygen consumption for cross-country skiers has been also confirmed by some studies showing a relationship between these test variables and competitive performance capacity of cross-country skiing [7,8].…”
Section: Introductionmentioning
confidence: 58%
“…Before exercising a single 60 seconds test, subjects relaxed for an additional 5 minutes. After that, subjects performed a single 60 seconds test during which the aim was to achieve the maximum average power output over the entire 60 seconds when starting from the last stop (Alsobrook & Heil, 2009).…”
Section: Dataset Generationmentioning
confidence: 99%
“…Moreover, there is no standardization in measurement protocol of UBP. Consequently, it may be advantageous to predict rather than measure UBP using actual training data previously collected by tests on ergometers (Alsobrook & Heil, 2009). …”
Section: Introductionmentioning
confidence: 99%